A Neglected Point: Frailty in Older Adults with Differentiated Thyroid Cancer - Meric Coskun; Esra Cataltepe; Hacer Dogan Varan; Eda Ceker; Yasemin Bektas; Yasemin Kuscu; Mehmet Muhittin Yalcin; Mujde Akturk; Fusun Balos Toruner; Mehmet Ayhan Karakoc; Alev Eroglu Altinova (Endocrinology and Metabolism)
Background This study investigated the risk of frailty in older adults with differentiated thyroid cancer (DTC) and the effect of thyroid-stimulating hormone (TSH) levels on frailty. Methods This single-center, cross-sectional study included 70 DTC patients aged ≥60 years with stable TSH levels during the previous year while receiving levothyroxine. Frailty was assessed using the fried frailty phenotype (FFP). Anterior thigh muscle thickness was measured by ultrasound, and the sonographic thigh adjustment ratio (STAR) index was calculated. Muscle strength was measured using a hand dynamometer. Physical activity was determined by the physical activity scale for the elderly (PASE). Results The median (interquartile range) age and follow-up time were 65 years (62 to 71) and 11 years (7.0 to 14.2), respectively. The median TSH level was 1.10 μIU/mL (0.49 to 1.62), and 58.6% of patients were prefrail/frail. Muscle mass and strength were reduced in 35.7% and 17.2% of patients, respectively. TSH levels were lower in those with prefrailty/frailty (P=0.002), low muscle mass (P=0.014), and low strength (P=0.037) than in their normal counterparts. TSH levels correlated negatively with FFP (P=0.001) and positively with the STAR index (P=0.034). TSH below 1.325 μIU/mL was associated with an increased frailty risk (area under the curve=0.719; P=0.001). Low TSH, female sex, low handgrip strength, and low PASE leisure time scores emerged as independent predictors of frailty (P<0.05). Conclusion Older adults with lower TSH levels due to DTC are at high frailty risk and have low muscle mass and strength. Therefore, TSH targets should be set based on a comprehensive evaluation with consideration of the risk-benefit ratio.